Population variation and natural selection on leaf traits in cork oak throughout its distribution range (Acta Oecologica, 2014)
A central issue in evolutionary biology is the exploration of functional trait variation among populations and the extent to which this variation has adaptive value. It was recently proposed that specific leaf area (SLA), leaf nitrogen concentration per mass (Nmass) and water use efficiency in cork oak play an important role in adaptation to water availability in the environment. In order to investigate this hypothesis, we explored, first, whether there was population-level variation in cork oak (Quercus suber) for these functional traits throughout its distribution range; if this were the case, it would be consistent with the hypothesis that different rainfall patterns have led to ecotypic differentiation in this species. Second, we studied whether the population-level variation matched short-term selection on these traits under different water availability conditions using two fitness components: survival and growth. We found high population-level differentiation in SLA and Nmass, with populations from dry places exhibiting the lowest values for SLA and Nmass. Likewise, reduced SLA had fitness benefits in terms of growth for plants under dry conditions. However, contrary to our expectations, we did not find any pattern of association between functional traits and survival in nine-year-old saplings despite considerable drought during one year of the study period. These results together with findings from the literature suggest that early stages of development are the most critical period for this species. Most importantly, these findings suggest that cork oak saplings have a considerable potential to cope with dry conditions. This capacity to withstand aridity has important implications for conservation of cork oak woodlands under the ongoing climate change.